Avian vampire fly (Philornis downsi) mortality differs across Darwin’s finch host species - Lauren K. Common (Nature Portfolio, 2021)
Abstract In invasive parasites, generalism is considered advantageous during the initial phase of introduction. Thereafter, fitness costs to parasites, such as host-specific mortality, can drive parasites towards specialism to avoid costly hosts. It is important to determine changes in host specificity of invasive populations to understand host-parasite dynamics and their effects on vulnerable host populations. We examined changes in mortality in the introduced avian vampire fly (Philornis downsi) (Diptera: Muscidae), a generalist myasis-causing ectoparasite, between 2004 and 2020 on Floreana Island (Galápagos). Mortality was measured as the proportion of immature larvae found upon host nest termination. Over the time period, the avian vampire fly was most abundant and had low mortality in nests of the critically endangered medium tree finch (Camarhynchus pauper) and had the highest mortality in nests of hybrid tree finches (Camarhynchus spp.). Low larval mortality was also found in small tree (Camarhynchus parvulus) and small ground finch (Geospiza fuliginosa) nests. Selection could favour avian vampire flies that select medium tree finch nests and/or avoid hybrid nests. Overall, the finding of differences in avian vampire fly survival across host species is parsimonious with the idea that the introduced fly may be evolving towards host specialisation.